The Impact of Islam on the Organizational Commitment of Athletes - Ünlü Yilmaz, Adem Solakumur, Zeki Taş (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Based on the scriptures of the religion of Islam, which obliges its followers to work, loyalty and honesty, as seen in the verses and hadiths, this study aims to examine the impact of the religion of Islam on the organizational commitment of athletes, who are one of the most important stakeholders of sports. Method: In the research, "Organizational Commitment Scale (OCS) and "Islamic Religion’s Impact on Sports Activites Scale (IRISAS) were used to determine the organizational commitment of the athletes and the impact of Islam in sports activities. Research data were obtained from 365 athletes according to the convenience sampling technique. The survey model was used in the study, which was conducted as a field study. For this purpose, distributions of demographic characteristics are shown with ratio, frequency and percentage. In addition, the correlation status between “Age”, “OCS”, and “IRISAS” were tested with the Correlation test. Regression analysis was also applied to determine the impact of Islamic religion on the organizational commitment of the athletes. Results: According to the findings, it has been determined that there is a positive and significant relationship between "age" and "organizational commitment" and "Islamic religious impact in sports activities". Conclusion: As a result of the regression analysis, it was determined that the impact of Islam in sports activities significantly predicted the organizational commitment of the athletes.